PENGARUH LITERASI KEUANGAN TERHADAP PENINGKATAN KINERJA KEUANGAN UMKM PENGRAJIN BATIK DI SURAKARTA - Dewi Ayu Puspitasari; Edi Wibowo; Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the influence of financial literacy knowledge, understanding financial literacy, financial management, on improving financial performance. This research is a survey research on the UMKM owners of batik craftsmen in Surakarta Types of data using quantitative and descriptive data. Data source data uses primary data and secondary data. The population in this study was UMKM of batik craftsmen in Surakarta consisting of 5 subdistricts. Data collection techniques using questionnaires, literature study and observation. The classic assumption test of this research uses multicollinearity test, autocorrelation test, heteroscedasticity test and normality. Data analysis techniques used descriptive analysis, multiple linear regression analysis, t test, F test (simultaneous) and the coefficient of determination test.